Mitochondria and mitochondrial ROS in cancer: novel targets for anticancer therapy - Yang, Yuhui; Karakhanova, Svetlana; Bazhin, Alexandr V. (Journal of cellular physiology, 2016)
Mitochondria are indispensable for energy metabolism, apoptosis regulation, and cell signaling. Mitochondria in malignant cells differ structurally and functionally from those in normal cells and participate actively in metabolic reprogramming. Mitochondria in cancer cells are characterized by reactive oxygen species (ROS) overproduction, which promotes cancer development by inducing genomic instability, modifying gene expression, and participating in signaling pathways. Mitochondrial and nuclear DNA mutations caused by oxidative damage that impair the oxidative phosphorylation process will result in further mitochondrial ROS production, completing the “vicious cycle” between mitochondria, ROS, genomic instability, and cancer development. The multiple essential roles of mitochondria have been utilized for designing novel mitochondria-targeted anticancer agents. Selective drug delivery to mitochondria helps to increase specificity and reduce toxicity of these agents. In order to reduce mitochondrial ROS production, mitochondria-targeted antioxidants can specifically accumulate in mitochondria by affiliating to a lipophilic penetrating cation and prevent mitochondria from oxidative damage. In consistence with the oncogenic role of ROS, mitochondria-targeted antioxidants are found to be effective in cancer prevention and anticancer therapy. A better understanding of the role played by mitochondria in cancer development will help to reveal more therapeutic targets, and will help to increase the activity and selectivity of mitochondria-targeted anticancer drugs. In this review we summarized the impact of mitochondria on cancer and gave summary about the possibilities to target mitochondria for anticancer therapies. J. Cell. Physiol. 231: 2570-2581, 2016. © 2016 Wiley Periodicals, Inc.
Gesehen am 31.10.2019